RISK FINANCING TECHNIQUES AND SMEs PERFORMANCE: EMPIRICAL EVIDENCE FROM NIGERIA - AJEMUNIGBOHUN, Sunday Stephen; IPIGANSI , Pretoria (Annals of Spiru Haret University. Economic Series, 2023)
Risk financing is a critical element of a resilient future. Risk management techniques are important metrics in safeguarding the lives and property of mankind. Therefore, this study aimed to assess the effects of financial risk management techniques on business performance, with specific reference to the perceptions of selected SMEs in Lagos, Nigeria. The study adopted a cross-sectional survey research design. The study population consisted of the total number of registered SMEs recorded in Lagos State at 11,666. Thus, single-stage cluster and convenience sampling techniques were employed in the questionnaire distribution and data collection processes. Two hundred and forty-eight (248) respondents were used in the study. The statistical technique employed was simple regression. This study confirms the importance of financial risk management techniques in business performance of selected SMEs operators in Lagos, Nigeria. It is recommended that insurance providers in Nigeria should attempt to tailor insurance products in a lovable and affordable manner to SMEs’ operators/owners in a bid to improve their behavioural risk attitudes. More so, interest should be placed on impressive risk management communication and ideal physical risk control techniques among SMEs’ owners/operators.